PARADIGMA PENDIDIKAN ISLAM: RAHMATAN LIL ‘ALAMIN (Gagasan dan Implikasinya dalam Pendidikan Islam) - Iis Arifudin (Jurnal Forum Tarbiyah, 2011)
Peace is one of the main features of the Islamic religion.In Alquran Surat al-Anbiya ‘(21) Paragraph 107 stated that Islam isa religion that brings mercy for all creatures. In other words, wheneverand wherever Muslims are, must provide guarantees for thesafety and peace of humanity around him. Not a threat, let alone theenemy. The principle of the Qur’an is based on the recognition ofIslam to universal humanity, because in principle, Islam is a universalreligion. Departing from the principles of the Koran, then in this paperattempt to explore the paradigm of Islamic education, where inits implementation through 3 (three) things: first, a paradigm shiftfrom teaching to educate teachers. Second, Islam is humanist educationand nonviolence. Third, educate inclusive attitude.